Peroxidases Bound to the Growing Lignin Polymer Produce Natural Like Extracellular Lignin in a Cell Culture of Norway Spruce - Warinowski, Tino; Koutaniemi, Sanna; Kärkönen, Anna; Sundberg, Ilari; Toikka, Merja; Simola, Liisa Kaarina; Kilpeläinen, Ilkka; Teeri, Teemu H. (Frontiers in Plant Science, 2016)
Lignin, an important component of plant cell walls, is a polymer of monolignols derived from the phenylpropanoid pathway. Monolignols are oxidized in the cell wall by oxidative enzymes (peroxidases and/or laccases) to radicals, which then couple with the growing lignin polymer. We have investigated the characteristics of the polymerization reaction by producing lignin polymers in vitro using different oxidative enzymes and analyzing the structures formed with NMR. The ability of the enzymes to oxidize a high-molecular-weight compounds was tested using cytochrome c as a substrate. The results support an idea that lignin structure is largely determined by the concentration ratios of the monolignol (coniferyl alcohol) and polymer radicals involved in the coupling reaction. High rate of the lignin polymer oxidation compared to monolignol oxidation leads to a natural-like structure. The high relative rate can be achieved by an open active site of the oxidative enzyme, close proximity of the enzyme with the polymeric substrate or simply by high enzymatic activity that consumes monolignols rapidly. Monolignols, which are oxidized efficiently, can be seen as competitive inhibitors of polymer oxidation. Our results indicate that, at least in a Norway spruce (Picea abies L. Karst.) cell culture, a group of apoplastic, polymer-oxidizing peroxidases bind to the lignin polymer and are responsible for production of natural-like lignin in cell suspension cultures in vivo, and also in vitro. The peroxidases bound to the extracellular lignin had the highest ability to bind to various cell wall polymers in vitro. Extracellular lignin contains pectin-type sugars, making them possible attachment points for these cationic peroxidases.